Building 21st Century Skills: Focusing on Creative Thinking Capability and Critical Thinking Ability - Alif Lukmanul Hakim; Darmawan Darmawan; Apit Fathurohman; Gamar Abdullah; Yasir Arafat (Universitas Muhammadiyah Enrekang, 2024)
Creative thinking and critical thinking skills have an increasingly important role in dealing with complexity and rapid change in the modern era. This research aims to illustrate the importance of skills in the 21st century, as well as describe the challenges in developing them and methods for strengthening learning. The research method used is a literature review with a qualitative descriptive approach, data is collected from various library sources such as scientific journals, books and related research reports. This study confirms that creative thinking and critical thinking skills are an important foundation in a holistic learning process, preparing individuals to face challenges in the ever-changing world of work. Challenges in developing these skills include changes in teacher roles, integration of technology, development of appropriate curricula, and project-based learning. However, by applying the right learning methods and relevant tips, future generations can be well prepared to become successful leaders and innovators in the modern era. The results of this study provide deep insight into the importance of creative thinking and critical thinking skills in the 21st century, and show the need for a holistic and innovative learning approach to prepare individuals to face future challenges.